The effectiveness of studying collocations by the Form 5 and 6 learners in Transcarpathian Hungarian schools in the English Lessons - Jacenta Krisztina (PoliPrint Kft., 2012)
Az idegen nyelvek tanítása kapcsán nagyon fontos hangsúly esik a szókincsfejlesztésre. Megtanulni beszélni egy idegen nyelven sokkal többet jelent attól, hogy tudjuk az adott nyelv összes nyelvtani és szemantikai szabályit. Fontos a tanulók szókincsének tudatos és folyamatos bővítése, ezen belül is a szókapcsolatok tanítása. Ebben a munkában a tanulók szókapcsolat-tanulásának hatékonyságát vizsgáltam.

Резюме. У процесі вивчення іноземної мови у початковій школі велику увагу звертають на розвиток словникового запасу учнів. Збагачення лексики традиційно вважається одним із найефективніших методів розвитку мовлення. Знання іноземної мови – це щось більше ніж знання граматичних і семантичних правил. Дуже важливо розвивати словниковий запас у початковій школі. Використовуючи різні форми навчання можна збагачувати його і досягти високих результатів у вивченні іноземної мови. У цій роботі я досліджувала як ефективно вивчаються словосполучення у школах.

Abstract. Effective vocabulary acquisition in a foreign language is particularly important for English Foreign Language learners who frequently acquire poor knowledge of the lexis despite the years of formal study. Based on the research of prominent linguists, I dealt with the problem of vocabulary learning and focused on collocations. I have carried out research in the Secondary School of Shalank and in School №3 in Nagyszőlős in Forms 5 and 6. The aim of my work was to find answers to the following questions: 1. Do the learners study the English language effectively? 2. Are the pupils motivated to study the English language? 3. Do the pupils study the collocations effectively?
http://kmf.uz.ua/hun114/letoltes/acta/Acta_2012_2.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00005840
Keywords: studying collocations; English Lessons; Transcarpathian Hungarian schools; Transcarpathia